System zarządzania jakością w jednostkach samorządu terytorialnego na przykładzie Urzędu Gminy Polkowice - Wysocka, Małgorzata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
In this paper a review of the quality management systems and the methods in the public administration has been made. On this background the quality management system in the Polkowice commune has been shown. The evaluation includes: the quality of the public services, the manners of the officials, the knowledge of the officials, the information system in the office and punctuality of the public services. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 673-689